2021
DOI: 10.1007/s11098-021-01661-w
|View full text |Cite
|
Sign up to set email alerts
|

Setting the story straight: fictionalism about grounding

Abstract: This paper explores a middle way between realism and eliminativism about grounding. Grounding-talk is intelligible and useful, but it fails to pick out grounding relations that exist or obtain in reality. Instead, grounding-talk allows us to convey facts about what metaphysically explains what, and about the worldly dependence relations that give rise to those explanations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…I have focused on Thompson's (2022) fictionalist proposal about grounding and shown that it is unmotivated. Perhaps there is another development of grounding fictionalism that will avoid my objections, but I cannot think of one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…I have focused on Thompson's (2022) fictionalist proposal about grounding and shown that it is unmotivated. Perhaps there is another development of grounding fictionalism that will avoid my objections, but I cannot think of one.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to Thompson (2022), grounding fictionalism is now officially on the table. Thompson defends hermeneutic fictionalism on which sentences about grounding are actually used non-literally to convey claims about what metaphysically explains what.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant antirealist accounts of grounding (e.g. Miller & Norton, 2017; Thompson, 2022) have as part of their motivation the idea that grounding is an explanatory relation, and that explanation should be understood as constrained along various epistemic, psychological, and pragmatic dimensions. Grounding‐first unionism might thus be a natural view for anybody who is already an antirealist about grounding.…”
Section: Unionism and Non‐unionismmentioning
confidence: 99%
“…7 Versions of antirealism about grounding are developed in Miller andNorton (2017, 2022) and in Thompson (2018Thompson ( , 2022.…”
Section: Antirealism About What Is Representedmentioning
confidence: 99%